2017
DOI: 10.1186/s12906-017-2036-1
|View full text |Cite
|
Sign up to set email alerts
|

MOK, a pharmacopuncture medicine, regulates thyroid dysfunction in L-thyroxin-induced hyperthyroidism in rats through the regulation of oxidation and the TRPV1 ion channel

Abstract: BackgroundIn this study, we evaluated the therapeutic effect of MOK, a pharmacopuncture medicine, on thyroid dysfunction in L-thyroxin (LT4)-induced hyperthyroidism rats.MethodsThe experimental hyperthyroidism model was prepared by the intraperitoneal injection of LT4 (0.5 mg/kg) once daily for 2 weeks in SD rats. MOK extract was injected at doses of 0.3 or 3 mg/kg on acupuncture points in the thyroid glands of LT4-induced hypothyroidism rats once a day for 2 weeks. The body temperature, body weight, and food/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 41 publications
2
13
0
1
Order By: Relevance
“…Specifically, MOK has been reported to exert anti-inflammatory effects in cell-based assays ( 14 ). Moreover, its in vivo anti-hypothyroidism and anti-hyperthyroidism effects have been confirmed in previous studies ( 15 , 16 ). In addition, its inhibitory function on the production of inflammatory mediators by primary peritoneal macrophages has been reported ( 17 ).…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Specifically, MOK has been reported to exert anti-inflammatory effects in cell-based assays ( 14 ). Moreover, its in vivo anti-hypothyroidism and anti-hyperthyroidism effects have been confirmed in previous studies ( 15 , 16 ). In addition, its inhibitory function on the production of inflammatory mediators by primary peritoneal macrophages has been reported ( 17 ).…”
Section: Introductionsupporting
confidence: 77%
“…Notably, these ten herbs have individually been reported to have anti-inflammatory and antioxidant properties ( 25 - 32 ). Additionally, in our previous high-performance liquid chromatography analysis of MOK extract, we detected several compounds, such as bilirubin, ursodeoxycholic acid, baicalein and muscone, that were also reported to have anti-inflammatory and antioxidant properties ( 15 ). Therefore, various pharmaceutical effects of MOK extract in pharmacopuncture therapy may be predicted based on the studies on the individual effects of MOK components in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 93%
“…Thyroid hormones normally promote metabolic conditions, characterized by weight loss, reduced levels of different serum lipids including cholesterol, TG and HDL 30,31 . In this study, similar to our earlier finding 10 decreased levels of TC, TG, HDL-C, LDL-C, and VLDL-C were observed in thyrotoxic rats; whereas, treatment with APC restored all these serum lipids near to their normal levels in T 4 -treated rats, further supporting its beneficial effects in thyrotoxicosis.…”
Section: Discussionmentioning
confidence: 99%
“…and animals of group 3 received only APC by oral route for 30 days. The doses here we used for PTU and T 4 were taken from our previous published work 31 . To avoid the circadian interference, all the treatments were scheduled between 10.00 and 11.00 h of the day and the total duration of the experiment was 6 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Some randomized controlled trials reported that Traditional Chinese medicine (TCM) is an effective and alternative therapy for AITDs (7)(8)(9). TCM is reported to be effective on relieving symptoms, decreasing levels of thyroid antibodies, alleviating follicular destruction and improving the quality of life with few side effects (10)(11)(12). JiaYanKangTai (JYKT) is a Chinese patent medicine, numbered ZL 2016 1 0642433.6, which is composed of 10 g of Bupleuri Radix, 20 g of Curcumae Radix, 30 g of Prunellae Spica, 15 g of Mume Fructus, 15 g of Fritillariae Thunbergii Bulbus, 10 g of Scrophulariae Radix, 10 g of Dioscoreae Nipponicae Rhizoma, 6 g of Cremastrae Pseudobulbus and 30 g of Astragali Radix (13,14).…”
Section: Introductionmentioning
confidence: 99%